1989
DOI: 10.1111/j.1550-7408.1989.tb01091.x
|View full text |Cite
|
Sign up to set email alerts
|

Binding of Lectins to Culture and Vector Forms of Trypanosoma rangeli Tejera, 1920 (Protozoa, Kinetoplastida) and to Structures of the Vector Gut

Abstract: Culture forms of Trypanosoma rangeli could be agglutinated with Canavalia ensiformis (Con A) lectin and, less effectively with Pisum sativum agglutinin (PEA), at a concentration of 200 micrograms/ml. Ricinus communis agglutinin I (RCA I) agglutinated trypanosomes only if they were not previously washed with physiological Ringer's solution. Three other lectins did not react with the same parasite forms. Direct or indirect lectin-gold labeling techniques were applied to LR-White embedded thin sections of T. rang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

1990
1990
2009
2009

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 33 publications
0
2
0
1
Order By: Relevance
“…Importante campo de estudios ha sido también el uso de lectinas, como marcadores de la composición de los resíduos de azúcares en la superficie de T. rangeli 42 58 . Observaciones con ConA y PEA (Pisum sativum) hechas con formas de cultivo, de la hemolinfa y también, en los tejidos de los insectos infectados, sugieren que, las variaciones de esos azúcares en la superficie del tripanosoma permitirían explicar por qué algunas cepas de T. rangeli, se adaptan mejor a algunas especies de triatominos y son más propicias para evolucionar en los insectos, que otras 51 . Significativo aporte ha surgido ultimamente del arsenal de herramientas de la biología molecular 49 62 Tanaka et al 64 y Henrikson et al 30 en sus estudios de kariotipaje molecular de T. rangeli, usando el sistema de Pulse Field Gel Electrophoresis, PFGE e hibridización con diversas sondas moleculares, fueron capaces de identificar bandas cromosómicas específicas de T. rangeli, que permitirían clara distinción con las de T. cruzi.…”
Section: Key-wordsunclassified
“…Importante campo de estudios ha sido también el uso de lectinas, como marcadores de la composición de los resíduos de azúcares en la superficie de T. rangeli 42 58 . Observaciones con ConA y PEA (Pisum sativum) hechas con formas de cultivo, de la hemolinfa y también, en los tejidos de los insectos infectados, sugieren que, las variaciones de esos azúcares en la superficie del tripanosoma permitirían explicar por qué algunas cepas de T. rangeli, se adaptan mejor a algunas especies de triatominos y son más propicias para evolucionar en los insectos, que otras 51 . Significativo aporte ha surgido ultimamente del arsenal de herramientas de la biología molecular 49 62 Tanaka et al 64 y Henrikson et al 30 en sus estudios de kariotipaje molecular de T. rangeli, usando el sistema de Pulse Field Gel Electrophoresis, PFGE e hibridización con diversas sondas moleculares, fueron capaces de identificar bandas cromosómicas específicas de T. rangeli, que permitirían clara distinción con las de T. cruzi.…”
Section: Key-wordsunclassified
“…According to several studies (Horisberger 1984;Benhamou and Ouellette 1986;Morioka et al 1987;Rudin et al 1989), thin sections of various pathogenic agents can be labeled with gold particle-conjugated lectins. Mannose was found in the cell walls and in some vacuoles after labeling of thin sections of Candida utilis with gold particle-conjugated Con A (Horisberger 1984).…”
Section: Discussionmentioning
confidence: 99%
“…Morioka et al (1987) reported the labeling of thin sections of Escherichia coli with WGA-gold complex. Rudin et al (1989) labeled thin sections of two Although we employed several methods (chemical ®xation of T. vaginalis cells, thermal polymerisation of resin and the freeze-substitution technique, UV polymerisation of resin) to prepare T. vaginalis cells for electron microscopy, no label was observed after exposure of thin sections of T. vaginalis to various gold particle-conjugated lectins (Figs. 2, 3).…”
Section: Discussionmentioning
confidence: 99%